The stratigraphy and chronology of the fluvial sediments at Warsash, UK: implications for the Palaeolithic archaeology of the River Test. Issue 2 (April 2017) - Hatch, Marcus; Davis, Robert J.; Lewis, Simon G.; Ashton, Nick; Briant, Rebecca M.; Lukas, Sven
Abstract: This paper reports new fieldwork at Warsash which clarifies the terrace stratigraphic framework of the Palaeolithic archaeology of the region. Sections were recorded in former gravel pits and at coastal locations, supplemented by the use of ground penetrating radar and luminescence dating techniques. The region's extensive borehole archive was also analysed to produce a revised terrace stratigraphy at Warsash and for the Test valley as a whole. At Warsash, some of the sediments previously identified as the Mottisfont/Lower Warsash Terrace are reassigned to the Hamble, Belbin/Upper Warsash and Ganger Wood/Mallards Moor Terraces. A luminescence dating programme, using test procedures not utilised in earlier dating studies in the region, yielded age estimates for the Hamble and Mottisfont/Lower Warsash Terraces at Warsash and also highlighted the complicated nature of the fluvial sediments of the River Test, suggesting that published luminescence ages for these deposits should be treated with some caution. This study indicates that the data used to construct terrace stratigraphies also requires careful assessment. The use of bedrock height and sediment thickness data produces more coherent long profile correlations than those produced by terrace surface data alone. The revised terrace stratigraphy provides the framework for the Palaeolithic archaeology at Warsash and clarifies correlations within and between archaeologically important sediments of the Test Valley, enabling it to contribute to discussions on the Lower-Middle Pleistocene settlement history of southern Britain.